Incident characterization of health conditions in women suspected of being victims of intimate partner violence - Mireille Sam; Joana Barrocas; Maria Clemente-Teixeira; Tiago Taveira-Gomes; Maria João Vidal-Alves; Teresa Magalhães (PLoS ONE, 2025)
Intimate partner violence (IPV) is a serious public health problem due to its severe health outcomes and its association with significant morbidity and mortality. There are many prevalence studies about this topic but few on incidence. Therefore, an incident health characterization of alleged IPV victims may be relevant to understanding the situation of the person at the moment when the suspicion of violence was recorded. The global aim is to characterize the health conditions of women allegedly victims of IPV. Specifically, the study aims to characterize: (a) health risk behaviours; (b) traumatic injuries and intoxications; (c) mental health disorders; and (d) physical disorders. We conducted a retrospective cohort study based on secondary data analysis of electronic health records and health registry data of patients of the Local Health Unit of Matosinhos (Portugal) between 2001 and 2021. To analyse variables, we selected official codes and regular terms used by physicians to describe violence during any clinical encounter. A total of 16 966 alleged female victims of IPV were identified along with a matched population of 29 980 women. This study highlights the significant increase in incidence rates of various health conditions among those allegedly victimized compared to the matched population. It provides novel insights by comparing incidence rates with previous prevalence estimates, revealing higher incidence ratios across the majority of health conditions among allegedly female IPV victims. This suggests a potential loss of follow-up among these individuals, possibly due to treatment dropout or mortality, highlighting the urgent need for targeted interventions and enhanced healthcare support for IPV victims.